Pemodelan Sistem Antrian Untuk Meningkatkan Efisiensi Layanan Di Rumah Sakit Hosana Medika Lippo Cikarang - Ruliyanti, Silvia Ami; Huda, Miftakul; Junaedi, Ridwan; Azizah, Ira Maelani; Dwi Ramdani, Moh Rizky (UNIVERSITAS SERAMBI MEKKAH, 2025)
To improve hospital service efficiency, this article analyzes and develops queue system modeling. The study uses the M/M/1 model to evaluate utilization ratios, waiting times, and discrete event simulation to predict the impact of service capacity changes. Data were collected through direct observation at the pharmacy, specialist clinics, and emergency department (ED), as well as patient satisfaction surveys conducted before and after the intervention. Results show that adjusting service capacity can reduce waiting times in the ED by up to 50% and increase patient satisfaction across all units by 30%. The conclusion is that queue system modeling based on empirical data can enhance operational efficiency and the quality of services provided by the hospital.